The importance of a creative approach and role playing in the development of language competence in studying foreign languages of students of agrarian universities - Chornobai, Vira; Чорнобай, Віра Георгіївна (My University, 2021)
University education acquires the features of a multicultural education. There is an active desire to integrate different types of higher institutions into scientific and educational megalopolises of continental, interregional and national importance. In many developed countries, universities are merging with agricultural and industrial enterprises. Role-playing games are actively used in teaching English not only for children, but also for adults. Університетська освіта набуває риси полікультурної освіти. Має бути активним бажання інтегрувати різні типи вузів в наукові і освітні мегаполіси континентального, міжрегіонального та національного значення. У багатьох розвинених країнах університети об'єднуються з сільськогосподарськими та промисловими підприємствами. Рольові ігри активно використовуються в навчанні англійської мови не тільки дітей, а й дорослих.
Важливість творчого підходу і рольових ігор у розвитку мовний компетентності у вивченні іноземних мов студентів аграрних ЗВО
Keywords: higher education; вища освіта; creativity; творчий підхід; role-playing games; рольові ігри; language competence; мовна компетентність; learning foreign languages; вивчення іноземних мов